Implementation Of Explanation Media In Knowledge About Lifestyle On The Event Of Hypertension In The Elderly In The Health Center Area Jongaya, Tamalate District Makassar City - Rahma Sri Susanti (Jurnal Komunitas Kesehatan Masyarakat, 2022)
Hypertension is still a major public health problem. The prevalence of hypertension in the elderly age group experienced a fairly high increase in cases of 63.2% (65-74 years) and 69.5% (>75 years). The purpose of this study was to determine the effect of counseling media in knowledge about lifestyle on the incidence of hypertension in the elderly in the Jongaya Community Health Center, Tamalate District, Makassar City. The research method used is Experiment with Quasi-Experimental design. Sampling was done by total sampling. The sample size is 63. The results of the Paired Sample T-Test analysis show that there is an effect of Pre-test and Post-test counseling on knowledge of smoking habits with the incidence of hypertension sig value (0.002), there is an effect of Pre-test and Post-test counseling on knowledge of the habit of consuming fatty foods. with the incidence of hypertension sig value (0.00) there is an effect of Pre-test and Post-test counseling on knowledge of habits of doing physical activity with the incidence of hypertension sig value (0.003). The conclusion from the 63 samples can be concluded that there is an influence of counseling media on knowledge about lifestyle (smoking habits, consumption habits of fatty foods and the habit of doing physical activity with hypertension. Based on the results of the research above, it is recommended that the public can prevent early onset of hypertension by improve a healthier lifestyle.